Simulating storm flooding maps over HafenCity under present and sea level rise scenarios. Issue 4 (31st July 2013) - Ge, J.; Much, D.; Kappenberg, J.; Nino, O.; Ding, P.; Chen, Z.
Abstract Global climate models have predicted a mean sea level rise between 0.18 m and 0.59 m by the end of the 21st century with high regional variability. The projected sea level rise due to global warming would inundate low‐lying areas. A high‐resolution unstructured‐grid Finite‐Volume Coastal and Ocean Model is applied to perform a simulation and prediction of the flooding process because of storm impacts around HafenCity under today's conditions and under scenarios of future sea level rise. The results show significant flooding under strong storm processes, such as the winter storm 'Anatol' in 1999. The flood coverage will be significantly increased under short‐, middle‐ and long‐term sea level rise scenarios. The peak flood levels will rise according to the respective sea level rise while the flood area will increase by 18% (2025), 34% (2055) and 54% (2085). The maximum flood height and area for the three sea level rise scenarios will reach ∼6.8 m and ∼4.1 × 105 m2, respectively. The most impacted area will be the region between the Baakenhafen (zone 12) and the Oberhafen/Oberhafenkanal. In the long‐term scenario (2085), flooding near the Magdeburger Hafen and Norderelbe will also increase. Coastal defence measures should be taken to ensure flood protection around HafenCity.